(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This research was carried out in the fish laboratory of the Department of Animal Production/College of Agriculture and Forestry/University of Mosul. 147 common carp, Cyprinus carpio L., were used with an average initial weight of 27.60 ± 2 gm/fish, distributed over seven experimental treatments, with three replicates for each treatment. The fish were acclimatized before the experiment for twenty-one days to the aquarium environment and food intake. Two types of organic chromium were added, namely chromium picolinate, at an amount of 0.3, 0.4, and 0.5 mg/kg feed (T2, T3, and T4), and 0.3, 0.4, and 0.5 mg/kg feed of chromium nicotinate (T5, T6, and T7), besides the control diet without additives (T1), which was balanced in terms of crude protein and metabolic energy. Results of the statistical analysis showed that the fish fed the experimental diets T3 and T7 were significantly superior (P? 0.05) in terms of hemoglobin and PCV to the rest of the experimental diets, including the control diet. Fish fed the T6 diet recorded a significant superiority over the rest of the other experimental treatments in the total blood protein and globulin standards, while no significant differences were observed between the different experimental treatments with the exception of the control diet, which was significantly behind the rest of the treatments in the albumin standard. Fish fed the control diet outperformed the parameters of blood sugar, triglycerides, AST, and ALT significantly more than the rest of the experimental treatments. It turns out that adding both types of organic chromium (organic chromium picolinate and nicotinate) at a rate of 0.5 mg/kg feed gave the best results in most of the criteria studied.